Review of Electrostatic Precipitator Device for Reduce of Diesel Engine Particulate Matter - Sudrajad, Agung; Ahmad Fitri, Yusop (Elsevier Ltd, 2015)
In the last few decades, electrostatic precipitators (ESP) have been modernized and many new methods have been implemented to increase in term of cleaning efficiency for particles in the sub micrometer size range. An electrical force has been implemented to increase the collection efficiency for removing particulate matter (PM) in the diesel engine. Based on results of particle properties and health effects studies, measurement systems are being discussed. This paper reviews the works that have been done in term of fundamental of ESP and electrical properties of ESP. The concept of ESP is ESPs only give electrostatic force to the particle. Thus, the gasses are not directly to the ESP and will results comparatively lower pressure drop. Therefore, the cost can be lowered down than the other filtration systems such as cyclonic and mechanical filtration. ESP In order to accumulate the charge by the particles, several factors will be taken into account such as particle size, dielectric constant and residence time in ESP. Also there are two type charging mechanism which are diffusion and field charging. The result of study is ESP can archive 99 percent of removal efficiency for a certain type of particulate.